Microbial resistance to antibiotics: state of knowledge and comments for the aquatic ecosystems - Gallegos-Rubianes, Aitana (2023)
Microbial resistance to antibiotics has been increasing over the years and is of great public health concern. Resistant bacteria spread in different ecosystems, highlighting anthropogenic activities as favoring the spread of these resistant bacteria; in many cases, they finally reach bodies of water where they can come into contact with humans. Different contaminants such as heavy metals and biocides can also be found in aquatic ecosystems, which increases the probability of a co-selection with antibiotic-resistant bacteria, which can aggravate the problem. The purpose of this review is to compile updated information on microbial resistance to antibiotics, commenting on its synergy with other water components such as heavy metals and biocides. Current information on resistance mechanisms, its spread in aquatic ecosystems, and current trends in antibiotic resistance in ecosystems are explored and synthesized.